Guidance on Preparation for Learning and Concentration of Autistic Children in the Urban Village of Surabaya: A Multicultural Guidance Study - Mierrina, Mierrina; Hendraswari, Febrina Prahesti; Widiyana, Finna Astri (Jurusan Bimbingan dan Konseling Islam, 2023)
The population density observed in one of the settlements in Surabaya poses a challenge in the process of equitable distribution of access to education and the socialization related to the stages of child growth and development, consequently affecting the community's awareness regarding the stages of child growth and development. Children with autism spectrum disorder experience developmental delays, yet they have the same rights as other children with typical development. The development of autistic children differs from that of their peers; they often exhibit specific patterns and require a high degree of consistency. Autistic children require support from various parties to optimize their abilities. The methodology employed in this research is qualitative, utilizing a case study model. This study employs an individual support program plan, with the subjects being children with autism spectrum disorder residing in a shelter in one of the settlements in Surabaya. The researcher's objective in implementing the Applied Behavior Therapy (ABA) method is to enhance self-readiness and concentration in autistic children.